Electrochemical behaviour of naked sub-nanometre sized copper clusters and effect of CO2. Issue 18 (25th August 2016) - Passalacqua, Rosalba; Parathoner, Siglinda; Centi, Gabriele; Halder, Avik; Tyo, Eric C.; Yang, Bing; Seifert, Sönke; Vajda, Stefan
Abstract : In size-controlled naked Cu5 and Cu20 nanoclusters the latter show anodic redox processes occurring at much lower potential with respect to Cu5, but the latter coordinate effectively CO2 and allow to reduce CO2 under cathodic conditions at lower overpotential. Abstract : The study of the electrochemical behavior (in the presence of N2 or CO2 ) of size-controlled naked Cu5 and Cu20 nanoclusters, prepared using a combination of gas-phase cluster ion sources, mass spectrometry, and soft-landing techniques, evidences some relevant results regarding the redox behavior of these sub-nanometre sized copper particles and the effect of CO2 on them. Cu20 nanoclusters show anodic redox processes occurring at much lower potential with respect to Cu5 nanoclusters, which behave relatively similar to much larger Cu particles. However, Cu5 nanoclusters coordinate effectively CO2 (hydrogen carbonate) in solution, different from Cu20 nanoclusters and larger Cu particles. This effect, rather than the redox behavior, is apparently connected to the ability of Cu5 nanoclusters to reduce CO2 under cathodic conditions at low overpotential. Although preliminary, these results provide rather exciting indications on the possibility of realizing low overpotential electrocatalytic conversion of CO2 .